2022
DOI: 10.1007/s10815-022-02395-2
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of FPR2 expression inhibits inflammation in preeclampsia by improving the biological functions of trophoblast via NF-κB pathway

Abstract: Purpose The dysfunction of trophoblast during inflammation plays an important role in PE. Formyl peptide receptor 2 (FPR2) plays crucial roles in the development of inflammation-associated disease. This present study aimed to explore the effect of FPR2 on a trophoblast cellular model of preeclampsia. Methods The expression of FPR2 in placenta was detected by immunohistochemical staining and western blotting. Transfection of siRNA was used to knockdown FPR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For example, Junaid et al found that thrombotic inflammatory disease could be alleviated through the AnxA1/FPR2/ALX pathway Ansari et al (2021). Inhibition of FPR2 expression via the NF-κB signaling pathway attenuates the effects of lipopolysaccharide-induced inflammation on trophoblast cells in pre-eclampsia (Li et al, 2022b). To alleviate chorioamnionitis, Li et al (2020) found that RvD1 attenuated trophoblast inflammation in vivo and in vitro via the FPR2/PPARγ/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Junaid et al found that thrombotic inflammatory disease could be alleviated through the AnxA1/FPR2/ALX pathway Ansari et al (2021). Inhibition of FPR2 expression via the NF-κB signaling pathway attenuates the effects of lipopolysaccharide-induced inflammation on trophoblast cells in pre-eclampsia (Li et al, 2022b). To alleviate chorioamnionitis, Li et al (2020) found that RvD1 attenuated trophoblast inflammation in vivo and in vitro via the FPR2/PPARγ/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The method of immunofluorescence was performed as previously described [ 52 ].Cells were fixed using 4% paraformaldehyde for 20 min at room temperature, permeabilized by 0.3% Triton X-100 for 10 min, blocked with 1xTBS with 3% BSA at room temperature for ∼30 min, incubated with primary antibody overnight at 4 °C, followed by incubation of the appropriate secondary antibody Primary antibodies used in this study were rabbit monoclonal anti-Sox2 (abcam, ab92494; 1/100 in 1xTBS with 3% BSA), rabbit monoclonal anti-Oct4 (abcam, ab181557; 1/100 in 1xTBS with 3% BSA). Secondary antibodies were anti-rabbit IgG labeled with Alexa Fluor 488, 550 (BOSTER, Cat# BA1105 and BA1090; 1/1000 in 1xTBS with 3% BSA).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Western blotting was applied to detect the protein expression levels in cells or tissues, as described previously ( Li et al, 2022 ). The antibodies used were listed in Supplementary file 4 .…”
Section: Methodsmentioning
confidence: 99%